COVID-19 Pandemic Impact on Public Distress, Economy and Education of Bago Division in Myanmar - Marnn, Phyoe; Htoo, Hsu; Zin, Phyo Moh Moh; Win, Thu Zar; Claude, Nizeyimana Jean; Ali, Haider; Al-Masnay, Yousef A.; Al-Shaibah, Bazel; Malik, Izhaar; Al-aizari, Ali R. (Technium Social Sciences Journal, 2021)
In Myanmar, two expatriates have started infected by COVID-19 pandemic on 23 March in 2020 and COVID-19 period was divided into the two periods by the data of patients, from starting July 29, no more infected people found till August 19. Myanmar citizen think that there will be no more new COVID-19 cases, they started running their daily work, not following precaution methods. Unfortunately, the number of patients increased more and more, starting from 20th August. The period between 23rd March and 19th August was regarded as COVID-19 first wave and the period starting from 10th August was COVID-19 second wave by Government. In Myanmar, numbers of developed city are fewer than rural townships. Infrastructures of townships are same and most people, living in rural townships are not rich and they didn’t have saving money in Banks and they are depending on their monthly salaries. During pandemic period, general workers faced with unemployment problem and difficulty in daily expenses. Some volunteers helped daily expenses to poor people in COVID-19 first wave. In second COVID-19 wave, volunteers cannot help many families. This paper focused on COVID-19 pandemic impact on Public psychological consequences, Economy, Educational dimension and the prospects after pandemic.